Effect of meteorological factors on rice sheath blight and exploratory development of a predictive model - BISWAS, BARUN; DHALIWAL, L K; CHAHAL, S K; PANNU, PPS (The Indian Journal of Agricultural Sciences, 2011)
Sheath blight disease has become an important constraint in rice crop cultivation in Punjab in recent years. A field experiment was conducted during rainy (kharif) of 2007 and 2008 to investigate the influence of different meteorological parameters on sheath blight development as well as computation of a predictive model to predict the disease well ahead its appearance in the field. Correlation analysis showed that among all the meteorological factors considered, maximum air temperature and morning relative humidity were key factors to govern the disease in the field. A maximum temperature around 34Â°C and a minimum temperature around 26Â°C were found to be favourable for the spread of sheath blight after its establishment in the field. Again high morning relative humidity more than 90% facilitates spreading of the disease. A predictive model was developed with a coefficient of determination (R2) of 0.8048 using statistical language R. A step-wise multiple regression analysis approach was adopted to identify the most appropriate predictive variables to constitute the model.